A Study on Reactive Ultra-Fine Fly Ash and Sulfoaluminate Cement in Self-Leveling Mortar - Pei-Min Chuang; Wei-Chung Yeih; Ran Huang; Jiang-Jhy Chang (Applied Sciences)
The purpose of this study is to find appropriate mixtures for self-leveling mortar that meet the fluidity requirements without displaying segregation by using a combination of two types of cement (Type I Portland cement and sulfoaluminate cement (SAC)) with reactive ultra-fine fly ash (RUFA). Unlike the fly ash, RUFA has a strong strength activity index and exhibits a significant pattern of amorphous phase in XRD. Appropriate mix proportions of raw materials, including the superplasticizer, require investigation in depth. A fixed water-to-binder ratio of 0.6 was selected, with varying proportions of the two cementitious materials considered (the SAC volume percentages were 0%, 10%, 20%, and 30%) and different RUFA contents (the RUFA volume percentages were 5%, 10%, and 15%). Twelve experiments were conducted to examine the properties of the self-leveling mortars. We found that a higher RUFA volume percentage results in lower porosity, higher compressive strength, and better resistance to drying shrinkage, abrasion, and restrained shrinkage cracking. Increasing the SAC volume percentage increases the porosity of self-leveling mortar and its early compressive strength but decreases late-stage strength. At a 10% volume percentage level, SAC achieves an ideal balance among drying shrinkage, brasion, and shrinkage cracking.